Geo-questionnaire in urban planning – preliminary results of the experimental application in Poland - Edyta Bąkowska; Tomasz Kaczmarek; Piotr Jankowski; Zbigniew Zwoliński; Łukasz Mikuła; Michał Czepkiewicz; Cezary Brudka (Rozwój Regionalny i Polityka Regionalna)
Changes in the attitude of local authorities towards the public participation in the decision making processes have prompted development of new methods of such involvement. As far as the urban planning is concerned, of particular potential is the so-called Public Participation Geographic Information Systems (PPGIS). One of the tools used for the purpose is a geo-questionnaire, combining the benefits of a standard questionnaire and a map, which permits collecting information on particular sites and on the respondents’ ideas on localisation of new objects and functionalities. Within the project “Geoportal supporting public participation in urban planning”, in the years 2015–2016, a study was undertaken to explore the effectiveness and usefulness of the geo-questionnaire. Five pilot studies were performed in the Poznań and Łódź agglomerations. The geo-questionnaires concerned the local spatial management plan in Rokietnica (Poznań agglomeration), landscape protection in Łódź, conception of the transportation system development in Łódź, conception of urban design of the Łazarski Market in Poznań, and the Map of Local Needs in the city center of Poznań. The aim of the study was to present the preliminary results of the initial implementations of geo-questionnaire developed within the project Geoportal supporting public participation in urban planning. The applications of geo-questionnaire have been analysed taking into account the characteristics of implementation areas, characteristics of users, the effectiveness of recruitment methods and opinions about the tool from two points of view: the respondents and the recipients of results.